Application of the Salam Agreement Toward the Settlement of Disputes over the Sale and Purchase of Candlenuts in Nalui Village, Jaro Subdistrict - Isnaniah; Dr. H. Hamdan Mahmud, M.Ag (Interdisciplinary Explorations in Research Journal, 2024)
Abstract This research discusses the implementation of the salam contract in the candlenut sale and purchase transaction, with a focus on the problems that arise from the seller's non-compliance with his obligations. The cases in this study include receiving goods that are not as ordered and defective, which results in unwillingness and loss on the part of the buyer. This study aims to understand the implementation of the salam contract in the sale and purchase of candlenuts and to find solutions to problems that arise during the transaction process. The research method used is a qualitative approach with a field research design and data collection techniques through interviews. The results of the study revealed two cases related to the implementation of the salam contract that did not meet the standards. Defective goods and buyer's unwillingness are the main problems in cases of implementation of contracts that do not meet the standards. The findings provide valuable insights to improve the implementation of the salam contract in candlenut trading, emphasizing the need to improve the quality of order preparation and enforcement of transaction standards. Keywords: Salam Agreement, Khiyar, Disputes, Abstrak Penelitian ini membahas pelaksanaan akad salam dalam transaksi jual beli kemiri, dengan fokus pada permasalahan yang timbul seiring ketidakpatuhan penjual terhadap kewajibannya. Kasus dalam penelitian ini mencakup penerimaan barang tidak sesuai pesanan dan cacat, yang mengakibatkan ketidakrelaan dan kerugian pada pihak pembeli. Penelitian ini bertujuan untuk memahami pelaksanaan akad salam dalam jual beli kemiri dan mencari solusi terhadap permasalahan yang muncul selama proses transaksi. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan desain penelitian lapangan dan teknik pengumpulan data melalui wawancara. Hasil penelitian mengungkap dua kasus terkait dengan pelaksanaan akad salam yang tidak sesuai standar. Barang cacat dan ketidakrelaan pembeli menjadi masalah utama pada kasus pelaksanaan akad yang tidak sesuai standar. Temuan ini memberikan wawasan yang berharga untuk meningkatkan pelaksanaan akad salam dalam jual beli kemiri, dengan menekankan perlunya peningkatan kualitas persiapan pesanan dan penegakan standar transaksi. Kata Kunci: Akad Salam, Khiyar, Sengketa